Analisis January Effect pada Saham Perusahaan LQ-45 di Bursa Efek Indonesia - Dwi Cahyaningdyah; Dhany Kurniawan Putra (Jurnal Maksipreneur, 2013)
The purpose of this research is to examine about the existence of a January Effect in the Indonesia stock exchange. Research samples used purposive sampling. Sample consists 30 companies based on sampling criteria. Analysis of data used one sample kolmogorov-smirnov to test data normality and to test hypotheses using one sample t-test. The result shows January Effect didn’t exist in Indonesia stock exchange in the period 2011- 2012. This can be seen that although the value of average return in January showed significant but the average return was not the highest, the highest average return was occurred on June.